Matthew Kelly (ed.), Nature and the Environment in Nineteenth Century Ireland, (Liverpool: Liverpool University Press, 2019). ISBN 978-1-78962-450-2, £75 (hardback). (2021) - Lacoste, Chloé
No abstract available